2001
DOI: 10.1074/jbc.m101400200
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin Protects Cerebellar Granule Neurons from Dopamine-induced Apoptosis by Dual Activation of the Ras-Phosphoinositide 3-Kinase and Jun N-terminal Kinase Pathways

Abstract: Excessive production of reactive oxygen species in living cells may damage their biological components. This condition, referred to as oxidative stress, is a common denominator of pathological conditions. Cells have evolved a wide array of antioxidant mechanisms including small reducing molecules (e.g. glutathione, ascorbic acid), antioxidative enzymes (e.g. catalase, superoxide dismutase, glutathione peroxidase; for review, see Refs. 1-4), and oxidoreductase enzymes such as thioredoxin and glutaredoxin (Grx) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 104 publications
(70 reference statements)
1
43
0
Order By: Relevance
“…Cytosolic Grx1 is implicated in several cellular processes that require strict redox control, for instance the regulation of transcription factors (18,53) and apoptosis (16,54,55). In this study, we have found that Grx1 itself is inhibited by oxidation and nitrosylation of structural Cys residues.…”
Section: Discussionmentioning
confidence: 48%
“…Cytosolic Grx1 is implicated in several cellular processes that require strict redox control, for instance the regulation of transcription factors (18,53) and apoptosis (16,54,55). In this study, we have found that Grx1 itself is inhibited by oxidation and nitrosylation of structural Cys residues.…”
Section: Discussionmentioning
confidence: 48%
“…Thirdly, the use of cell death as an end point may not be appropriate for correlating the extent of cell injury to the level of protein S-glutathionylation. Nevertheless, overexpression of Grx1 has been shown to prevent cells from oxidant-mediated damage in response to dopamine, H 2 O 2 , and high concentrations of glucose [26][27][28][29][30][31]. These results support the hypothesis that oxidant-induced cell injury is partly mediated through S-glutathionylation of proteins.…”
Section: Discussionmentioning
confidence: 63%
“…As expected, cells overexpressing Grx1 are more resistant to doxorubicin-induced toxicity compared to control cells [26]. In addition, treatment of cultured cerebellar granule neurons with recombinant Grx protein of E. coli prevents cell death induced by dopamine, and the protection appears to be mediated through activation of the Ras/PI3K/ Ref-1/Akt/NF-κB pathway [27,28]. This protective mechanism was further elaborated in another study in which Grx1 overexpression was shown to protect H9c2 cells against toxicity of hydrogen peroxide (H 2 O 2 ) [29].…”
Section: Introductionmentioning
confidence: 56%
“…Grx1 also protects cells from apotosis induced by hydrogen peroxide by regulating the redox state of Akt (46). Escherichia coli Grx2 and human Grx1 have been shown to protect cerebellular granulae neurons from dopamine-induced apoptosis, involving the Ras-phosphoinositide 3-kinase and Jun N-terminal kinase pathways (47,48). On the other hand, apoptosis signal-regulating kinase 1 is inactive when bound to reduced Grx1 (49), and oxidation of Grx1 causes release of apoptosis signal-regulating kinase 1 and hence initiation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%